Effects of intravenous phosphodiesterase inhibitors and corticosteroids on severe meconium aspiration syndrome. Issue 7 (July 2019) - Shao, Ju-Ing; Lin, Chih-Hsueh; Yang, Yi-Hsin; Jeng, Mei-Jy
Abstract : Background: Meconium aspiration syndrome (MAS) is a major cause of severe respiratory failure in near- and full-term neonates. Alleviating inflammation is key to successfully treating severe MAS. Phosphodiesterase (PDE) inhibitors are known to play a role in airway smooth muscle relaxation and alveolar inflammation inhibition. This study aimed to investigate the effects of various intravenous (IV) PDE inhibitors and corticosteroids on MAS. Methods: MAS was induced in newborn piglets by instilling human meconium in them. The piglets were randomly divided into five groups (n = 5 in each group): (1) control (sham treatment); (2) dexamethasone (Dex) (IV 0.6 mg/kg of dexamethasone); (3) aminophylline (Ami) (IV 6 mg/kg of aminophylline, followed by continuous infusion of 0.5 mg/kg/h of aminophylline; (4) milrinone (Mil) (IV 50 μg/kg of milrinone, followed by continuous infusion of 0.75 μg/kg/h of milrinone); and (5) rolipram (Rol) (IV 0.8 mg/kg of rolipram). The duration of the experimental period was 4 hours. Results: Compared to the control group, all the four treatment groups revealed better oxygenation 3 hours and more after the start of treatment. The Rol group had a significantly elevated heart beat ( p < 0.05) and relatively lower blood pressure compared to the other groups during the first 2 hours of the experiment. The Dex group had significantly lower interleukin (IL)-1β levels in the lung tissue compared to the other groups ( p < 0.05) and significantly lower IL-6 levels compared to the Ami and Mil groups ( p < 0.05). Lung histology showed slightly less inflammation and atelectasis in the Dex group compared to the other groups, but lung injury scores showed no significant between-group differences. Conclusion: Using IV corticosteroids or any type of PDE inhibitors has some beneficial effects in improving oxygenation in MAS. PDE inhibitors are not superior to IV corticosteroids; in fact, adverse cardiovascular effects occur with the phosphodiesterase type 4 (PDE4) inhibitor. Further investigations are required before using IV corticosteroids and PDE inhibitors in future clinical application.